CHALDA MAHASU FOLK DEITY AS A CULTURAL HERITAGE OF JAUNSARI TRIBE OF UTTARAKHAND - Gupta, Priti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The culture of the Jaunsari tribe of Jaunsar Bawar, a tribal area of Dehradun district of Uttarakhand, is very rich. The religious concepts and folk culture here are different from the Himalayan regions. In the cultural aspect, the folk deities of Jaunsar have played a major role, where witchcraft, folk beliefs, folk faiths, traditions, folk music, folk dances play an important role. For the people of Jaunsar, their deity is not only their guardian and protector but also their ruler and judge. Chalda Mahasu keeps traveling throughout the region throughout the year to listen to the sufferings of the people and to resolve them and to punish the criminals and to get justice for the victims. That is why the residents of Jaunsar have strong faith in his justice that they go to the court of the deity instead of going to the court. The court can punish those crimes or atrocities which cannot be decided in the court and after getting justice, they pledge to offer special offerings to the deity. He is also known as the God of Justice.